Antibiotic Policies Controlling Hospital Acquired Infection - Gould, Ian M.; Gould, Ian M.; van der Meer, Jos W.M.; van der Meer, Jos W.M. (Springer New York : Imprint: Springer, 2012)
Hospitals worldwide are currently suffering an epidemic of infections, generated in and spreading in those instituitions whose very “raison d’etre” is to protect and improve the health of their patients. This paradox comes at a time of possibly unprecedented investment in preventative measures (infection control). To better control these infections, however, we need to understand their causes, many of which are related, paradoxically, to the success of antibiotic therapy. It is possible that the golden era of antibiotics led subconsciously to a loss of emphasis on the importance of hygiene in the control of HAI. Moreover, the majority of HAIs are due to multiply antibiotic resistant bacteria whose emergence has been hastened by over-enthusiastic antibiotic prescribing. Accumulating evidence also suggests that antibiotics not only select for resistance but can actually increase the numbers of HAIs and even their virulence.   This comprehensive compilation, written by eminent international researchers, explores these hypothesis in the context of recent epidemiology and evidence for the success of various antibiotic stewardship measures in controlling and even reversing resistance. It contains chapters by acclaimed authors on all the major causes of HAI, including MRSA, VRE, Clostridium difficile and multi resistant gram negative infections which are increasingly pan-resistant and untreatable; the nearest thing we have yet experienced to a “Doomsday bug”.   This book is an excellent source of information for students, researchers and practitioners in infection control, hospital epidemiology, antimicrobial prescribing and microbiology.